2019
DOI: 10.1111/febs.15109
|View full text |Cite
|
Sign up to set email alerts
|

Structural conformation and self‐assembly process of p31‐43 gliadin peptide in aqueous solution. Implications for celiac disease

Abstract: Celiac disease (CeD) is a highly prevalent chronic immune-mediated enteropathy developed in genetically predisposed individuals after ingestion of a group of wheat proteins (called gliadins and glutenins). The 13mer agliadin peptide, p31-43, induces proinflammatory responses, observed by in vitro assays and animal models, that may contribute to innate immune mechanisms of CeD pathogenesis. Since a cellular receptor for p31-43 has not been identified, this raises the question of whether this peptide could media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 68 publications
(105 reference statements)
1
34
0
1
Order By: Relevance
“…Additionally, it can interconvert into other forms such as β-turns and β-strands because of the proximity of the corresponding dihedral angles [ 44 ]. PPII plays a vital role in protein–protein interactions [ 45 ] and aggregation, as it was detected as the intermediate motif during the self-aggregation of lysozyme [ 46 ], the Aβ-peptide [ 47 ] and gliadin peptides [ 48 , 49 ].…”
Section: Setting the Frame And Initial Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it can interconvert into other forms such as β-turns and β-strands because of the proximity of the corresponding dihedral angles [ 44 ]. PPII plays a vital role in protein–protein interactions [ 45 ] and aggregation, as it was detected as the intermediate motif during the self-aggregation of lysozyme [ 46 ], the Aβ-peptide [ 47 ] and gliadin peptides [ 48 , 49 ].…”
Section: Setting the Frame And Initial Considerationsmentioning
confidence: 99%
“…Recently, a Triazole-BODIPY-based probe was shown to detect, in a time-dependent manner, the first stages of Aβ-peptide oligomerization before fibril formation [ 104 ]. Additionally, the same BODIPY derivative identified the presence of oligomers of the toxic p31–43 peptide related to celiac disease [ 49 ]. This probe has proved to be a helpful tool in the rational screening of drugs that reduce peptide aggregation before the onset of disease.…”
Section: Fluorescence Spectroscopy Is a Versatile Tool For Evaluatmentioning
confidence: 99%
See 2 more Smart Citations
“…p31-43 was shown to inhibit the subunit of the chloride channel (CFTR) and thereby cause NF-kB activation, induction of IL-15 and TG2 activation, with a range of inflammatory consequences ( 88 ). Moreover, p31-43 is able to self-assemble in oligomers with potential important effects ( 89 ). In vivo analysis in a murine model showed that activation of the NLRP3 inflammasome, either by direct detection of oligomers or indirectly by sensing danger signals, is required for histological changes in the small intestinal mucosa ( 90 ).…”
Section: A Role For Gliadin Peptides In Causing An Innate Response?mentioning
confidence: 99%